A note on equilibrium Glauber and Kawasaki dynamics for fermion point processes - Ohlerich, N.; Lytvynov, E. W. (Methods of Functional Analysis and Topology, 2008)
We construct two types of equilibrium dynamics of infinite particle systems in a locally compact Polish space X, for which certain fermion point processes are invariant. The Glauber dynamics is a birth-and-death process in X, while in the case of the Kawasaki dynamics interacting particles randomly hop over X. We establish conditions on generators of both dynamics under which corresponding conservative Markov processes exist.